LINC00707 Regulates miR-382-5p/VEGFA Pathway to Enhance Cervical Cancer Progression - Hua Guo; Jing Li; Furong Fan; Ping Zhou (Journal of Immunology Research)
Long noncoding RNAs (LncRNAs) are reported to exhibit crucial roles in cancer progression. LINC00707 is recently indicated to be a significant oncogene in various cancers. Up to now, the mechanism of LINC00707 in cervical cancer is still unclear. In this study, our present work was designed to study the biological effects of LINC00707 in cervical cancer. Firstly, the expression level of LINC00707 in cervical cancer was tested. We observed LINC00707 expression was greatly increased in cervical cancer. Then, we assessed the detailed effect of LINC00707 on the development of cervical cancer using CCK-8 assay, Transwell assays, and tumor xenograft experiments. Gain-of-function and loss-of-function assays revealed the function of LINC00707 in cervical cancer progression. In addition, the action of LINC00707 in cervical cancer cells was studied using bioinformatic tools and luciferase reporter experiment. It was displayed that loss of LINC00707 significantly repressed cell growth of cervical cancer. Meanwhile, restoration of LINC00707 expression obviously induced cervical cancer cell growth. Then, we predicted that LINC00707 could serve as a molecular sponge for miR-382-5p to modulate VEGFA expression in cervical cancer. Subsequently, lack of VEGFA expression reversed the influence of miR-382-5p knockdown on cervical cancer cells. In conclusion, our findings evidenced the significant role of LINC00707-miR-382-5p-VEGFA network in cervical cancer and it can provide an attractive target.